2019
DOI: 10.1142/s1088424619300209
|View full text |Cite
|
Sign up to set email alerts
|

Dual function of lectins — new perspectives in targeted photodynamic therapy

Abstract: Porphyrins and phthalocyanines are photosensitizers (PS) that are used in clinical imaging, detection of cancer cells and are particularly applied in photodynamic therapy (PDT). Many scientists have been focused on the design of different porphyrin compounds. However, similar to other anti-cancer agents, they cannot selectively recognize tumor tissues. Scientists are seeking new methods to overcome this problem and to find appropriate targeted delivery strategies. Plant lectins are especially suitable molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 109 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…In addition, several plant lectins also displayed specific binding with hydrophobic ligands. These interactions occur at binding sites distinct from the carbohydrate-binding ones [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several plant lectins also displayed specific binding with hydrophobic ligands. These interactions occur at binding sites distinct from the carbohydrate-binding ones [25].…”
Section: Discussionmentioning
confidence: 99%
“…All these data motivated us to study the jacalin-curcumin interaction about the potential application of lectin as a drug carrier to cancer cells. Drug-protein complexes are important for biological systems [22][23][24][25][26][27][28]. Studying the molecular basis of the curcumin-protein interactions is important in designing novel therapeutic systems or improving selective drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Coumaryl 2-O-acetylated galactoside, that targets the Gal3 glycan recognition, can interfere with the Gal3-promoted sustained profibrotic cell signaling and scar formation [51] and we show that Au 3+ TPPS can bind this same site ( Figure 6A). Here, Au 3+ TPPS has the potential as a Gal3 inhibitor or as well as a photosensitizer in photodynamic therapy [38]. The 2nd docking site for Au 3+ TPPS is placed on a part of the Gal3 molecule that is not known to be directly involved in carbohydrate binding ( Figure 6B).…”
Section: Discussionmentioning
confidence: 99%
“…Lectins have been well studied for their non-covalent association with porphyrins and with photosensitizers in general (for a recent review see [38]), and crystal structures of concanavalin A [39], peanut agglutininin [40] and jacalin [41] plant lectins in complex with meso-tetrasulfonatophenylporphyrin (H(2)TPPS) show very convincing evidence of the attractiveness of their carbohydrate binding site for the porphyrin [39][40][41]. However, H(2)TPPS binds by intruding, overlapping or allosterically hindering the carbohydrate-binding sites of concanavalin A, peanut agglutininin and jacalin, respectively, therefore porphyrin binding might negatively interfere with the highly selective cancer-antigen targeting function of the plant lectins [38]. An earlier study demonstrated that zinc tetrasulfonatophenylporphyrin (Zn 2+ TTPS) binds Gal3 with high affinity (K d = 0.18 µM) [42], largely surpassing N-acetyllactosamine, that is generally considered to be a specific binder of Gal3, with reported affinities K d = 25 µM [43], 28 µM [44], 112 µM [45] and 118 µM [46].…”
Section: Introductionmentioning
confidence: 99%
“…Emerging work also illuminates their importance in many other biological processes, including nucleic acid synthesis and processing, signal transduction, and protein degradation, among many other cellular functions . Their medical appeal and relevance as photosensitizers in cancer treatment have also been amply demonstrated, especially in tumor imaging and photodynamic therapy. These properties could provide a means to use porphyrin binding and intrinsic physicochemical imaging attributes as GAL-7 markers in cancerous tissue progression. Here, we used a combination of cellular, nuclear magnetic resonance (NMR), small-angle X-ray scattering (SAXS), and molecular docking experiments to specifically alter GAL-7 function and characterize the effect of porphyrin binding on its molecular architecture.…”
mentioning
confidence: 99%